Phytochemical composition and bioactive effects of Salvia africana, salvia officinalis 'Icterina' and Salvia mexicana aqueous Extracts - Fernandes Afonso, Andrea Luísa (2018)
In the present study, aqueous extracts of Salvia africana, Salvia o cinalis ‘Icterina’ and Savia mexicana origin were screened for their phenolic composition and for antibacterial, antioxidant, anti-inflammatory and cytotoxic properties. The three aqueous extracts contained distinct phenolic compounds, with S. africana presenting the highest total levels (231.6 7.5 g/mg). Rosmarinic acid was the dominant phenolic compound in all extracts, yet that of S. africana origin was characterized by the present of yunnaneic acid isomers, which overall accounted for about 40% of total phenolics. In turn, S. o cinalis ‘Icterina’ extract presented glycosidic forms of apigenin, luteolin and scuttelarein, and the one obtained from S. mexicana contained several simple ca eic acid derivatives. S. africana aqueous extract exhibited high antioxidant potential in four methods, namely the DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging ability, iron-reducing power, inhibition of -carotene bleaching and of thiobarbituric acid reactive substances (TBARS), for which EC50 values were equal or only 1.3–3.1 higher than those of the standard compounds. Moreover, this extract was able to lower the levels of nitric oxide (NO) production in lipopolysaccharide (LPS)-activated RAW 264.7 macrophages (EC50 = 47.8 2.1 g/mL). In addition, the three sage aqueous extracts showed promising cytotoxic e ect towards hepatocellular HepG2, cervical HeLa, and breast carcinoma cells MCF-7. Overall this study highlights the potential of three little-exploited Salvia species, with commercial value for applications in food or pharmaceutical industries.